Análise quantitativa da expressão de genes relevantes para o envelhecimento e para a Doença de Alzheimer - Mazzotti, Tatiane Katsue Furuya [UNIFESP] (2011)
Alzheimer Disease is the most common cause of dementia in elderly people. This disorder is characterized by a complex neurodegenerative process affecting multiple genes and proteins. Therefore, efforts have been made in identifying differentially expressed genes to be used as biomarkers in conditions such as aging and Alzheimer fs Disease. Purpose: Quantitative expression analysis of LR11, SNAP25 and SIRT1 genes, involved respectively in APP processing, synaptic transmission and neuroprotection, were investigated in brain and blood tissues. Furthermore, the expression between both tissues was also compared in order to find systemic markers that could represent the brain. Methods: mRNA quantification was performed using qRT-PCR in three post mortem brain regions (entorhinal and auditory cortices and hippocampus) of 10 Alzheimer fs Disease patients and 10 healthy elderly as well as in peripheral blood lymphocytes of 25 young, 20 healthy elderly and 35 Alzheimer fs Disease patients. We used the ƒ¢ƒ¢CT method in the analysis and the 2-ƒ¢ƒ¢CT formula to calculate the relative quantification. Results: LR11 mRNA quantification did not differ significantly concerning brain regions between Alzheimer fs Disease and healthy elderly subjects. However, in lymphocytes, its expression was threefold higher in Alzheimer fs Disease and healthy elderly subjects in comparison to the young group. Regarding SIRT1 gene, its expression was twofold higher in Alzheimer fs Disease patients than in healthy elderly for all brain regions. In lymphocytes, however, SIRT1 mRNA quantification was not significantly different among the three studied groups. Furthermore, lymphocytes showed a higher gene expression than brain regions for both LR11 and SIRT1 genes. In addition, a lack of SNAP25 expression was observed in blood lymphocytes. In brain tissues of the healthy elderly group, SNAP25 mRNA quantification was lower in the entorhinal cortex and hippocampus than in the auditory cortex. Furthermore, relative quantification of SNAP25 mRNA in brain regions of Alzheimer fs Disease patients was 34-39% of the total expression observed in the healthy elderly group. Conclusions: Our results presented some potential markers of Alzheimer fs Disease and aging processes. LR11 expression may be considered an age-related marker in blood tissue. The higher SIRT1 expression in Alzheimer fs Disease patients f brain suggested that this gene might be involved in compensatory mechanisms in the late stages of Alzheimer fs Disease. Both LR11 and SIRT1 brain expression was not correlated with blood expression, not being possible to consider them as systemic biomarker of the disease. Furthermore, it was not possible to use SNAP25 gene as a biomarker in blood once it was not expressed in this tissue. However, in the Alzheimer’s Disease patients’ brain, the decrease of SNAP25 expression might suggest an impairment of the synaptic function and neurotransmission found in the disease.